2015
DOI: 10.1016/j.expneurol.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Seizure reduction through interneuron-mediated entrainment using low frequency optical stimulation

Abstract: Low frequency electrical stimulation (LFS) can reduce neural excitability and suppress seizures in animals and patients with epilepsy. However the therapeutic outcome could benefit from the determination of the cell types involved in seizure suppression. We used optogenetic techniques to investigate the role of interneurons in LFS (1Hz) in the epileptogenic hippocampus. Optical low frequency stimulation (oLFS) was first used to activate the cation channel channelrhodopsin-2 (ChR2) in the Thy1-ChR2 transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 57 publications
(67 reference statements)
3
45
2
Order By: Relevance
“…Low frequency stimulation has been used to suppress seizures through electrical stimulation 1821; 27; 3746 , repetitive transcranial magnetic stimulation (rTMS) 4750 , optically using optogenetics 51 , and even with auditory stimulation 52; 53 . Furthermore LFS has been applied to a number of different brain regions including the hippocampus 1821; 27; 38; 51 , cortex 41; 45 , amygdala 39 , anterior nucleus of the thalamus 42; 46 , Nucleus caudatus 37 , and to a wide variety of patient specific epileptic foci via rTMS 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low frequency stimulation has been used to suppress seizures through electrical stimulation 1821; 27; 3746 , repetitive transcranial magnetic stimulation (rTMS) 4750 , optically using optogenetics 51 , and even with auditory stimulation 52; 53 . Furthermore LFS has been applied to a number of different brain regions including the hippocampus 1821; 27; 38; 51 , cortex 41; 45 , amygdala 39 , anterior nucleus of the thalamus 42; 46 , Nucleus caudatus 37 , and to a wide variety of patient specific epileptic foci via rTMS 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore LFS has been applied to a number of different brain regions including the hippocampus 1821; 27; 38; 51 , cortex 41; 45 , amygdala 39 , anterior nucleus of the thalamus 42; 46 , Nucleus caudatus 37 , and to a wide variety of patient specific epileptic foci via rTMS 50 . The majority of these studies activate grey matter to achieve seizure suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optogenetics can shed light on these mechanisms by allowing cell-specific stimulations in animal models, the effects of which can then be compared with those of the global stimulation generated by DBS. For example, in a 4-aminopyridine model of acute seizures, optogenetic stimulation of interneurons, at frequencies standardly used with DBS (Koubeissi and others 2013), was sufficient to recapitulate the seizure suppressive effect observed when all neuronal cells were stimulated (Chiang and others 2014; Ladas and others 2015). Mechanistically, inhibitory cells appeared to initially induce a paradoxical excitatory bursting in pyramidal cells, which caused synchronization, and then ultimately suppression of pyramidal cell activity (Ladas and others 2015).…”
Section: Clinical Implications Of Optogenetic Studiesmentioning
confidence: 99%
“…Although the Thy1 promoter in general drives expression of transgenes in various types of neurons in the brain, the authors found that ChR2 expression was mostly localized to GABAergic interneurons in the hippocampus, suggesting that seizure suppression was achieved by enhancing inhibitory GABAergic inputs that counteracted over-excitation seen in the hippocampal circuitry. The same group went on to show that low frequency (1 Hz) optogenetic stimulation of hippocampal interneurons was able to entrain and suppress hyperactivity induced by 4-aminopyridine [55]. Synchronous activation of GABAergic interneurons resulted in synchronous pyramidal cell firing, which acted to reduce the overall hyperactivity of the hippocampus from prolonged afterhyperpolarizations after stimulation was stopped.…”
Section: Optogenetic Approaches To Treating Epilepsy In Vivomentioning
confidence: 99%